Exploring students testimonials on Speechahe pronunciation assessment: A qualitative investigation using narrative inquiry - R Muhammad Satria Gyas Mustagis; Setia Muljanto (JEELS (Journal of English Education and Linguistics Studies), 2026)
Abstract In Indonesian EFL contexts, accurate pronunciation is essential for effective communication and academic success, yet traditional teacher-centered approaches often fail to provide systematic assessment and individualized feedback. This study explores how high-achieving male undergraduate students perceive and utilize automated feedback from the SpeechAce Computer-Assisted Pronunciation Training (CAPT) platform in their pronunciation practice. Employing a qualitative narrative inquiry design, the study involved four second-semester male students at Institut Pendidikan Indonesia Garut who achieved scores above 7.0 on SpeechAce exercises. Data were collected through structured self-reflection prompts based on Thiel’s framework and analyzed using Labov’s six-stage narrative analysis model. The findings indicate that immediate and detailed automated feedback enhances learners’ metacognitive awareness, supports the development of hybrid learning strategies, and sustains motivation, leading to improvements in segmental accuracy and fluency. Participants also reported a shift from passive learning to active engagement in pronunciation practice. Despite limitations related to sample size, lack of a control group, and short intervention duration, the study suggests that integrating CAPT tools with structured reflective activities can effectively foster learner autonomy and support pedagogical innovation in EFL pronunciation instruction.